Effect of Gelatinization Temperature and Stirring Duration on Characteristics of Bioplastic Smart Packaging Film - Muthia, Anna Sukma; Yulianti, Ni Luh; Widia, I Wayan (Jurnal BETA (Biosistem dan Teknik Pertanian), 2022)
Packaging characteristics can be affected by gelatinization temperature and stirring duration. This research was conducted to obtain gelatinization temperature and stirring duration effect to bioplastic smart packaging film characteristics and to obtain a combination of gelatinization temperature and stirring duration that can produce the best packaging characteristic. The experimental design used was a Randomized Block Design (RBD) with the first-factor treatment is gelatinization temperature (T) which consisted of 3 levels: 75oC, 80oC, and 85oC. The second factor is stirring duration (D) which consisted of 3 levels: 5, 10 dan 15 minutes, with two repetitions to produce 18 experimental units. The data obtained were analyzed by using Analysis of variance (ANOVA) and if the treatment affected the observed parameters, the test was continued with Duncan's test. Gelatinization temperature treatment and stirring duration in the making of starch and bioplastic smart packaging affect the value of tensile strength, elongation, elasticity, water resistance, thickness, and color change of smart packaging films. The gelatinization temperature treatment of 80oC and the stirring duration of 5 minutes resulted in smart packaging with the characteristics of tensile strength of 14.10 MPa, elongation 3.73%, elasticity 397.75 MPa, water resistance 96.58%, and thickness 0.40mm and show responsive color changes.